Multiplexed transcriptomic analyzes of the plant embryonic hourglass - Hao Wu; Ruqiang Zhang; Karl J. Niklas; Michael J. Scanlon (Nature Communications)
Abstract Zoologists have adduced morphological convergence among embryonic stages of closely related taxa, which has been called the phylotypic stage of embryogenesis. Transcriptomic analyzes reveal an hourglass pattern of gene expression during plant and animal embryogenesis, characterized by the accumulation of evolutionarily older and conserved transcripts during mid-embryogenesis, whereas younger less-conserved transcripts predominate at earlier and later embryonic stages. In contrast, comparisons of embryonic gene expression among different animal phyla describe an inverse hourglass pattern, where expression is correlated during early and late stages but not during mid-embryo development. Here, multiplexed spatial-transcriptomic analyzes is used to investigate embryogenesis and homology in maize, which has grass-specific morphology. A set of shared, co-expressed genes is identified during initiation of maize embryonic organs, replete for ancient/conserved genes manifesting an hourglass pattern during mid-embryogenesis. Transcriptomic comparisons of maize and Arabidopsis embryogenesis with that of the moss Physcomitrium patens identify an inverse hourglass pattern across plant phyla, as in animals. The data suggest that the phylotypic stages in plants and animals are characterized by expression of ancient and conserved genes during histogenesis, organization of embryonic axes, and initial morphogenesis. We propose a mechanism for gene evolution during the innovation of morphological novelty.